Interferons in COVID-19: missed opportunities to prove efficacy in clinical phase III trials? - Brzoska, Josef; von Eick, Harald; Hündgen, Manfred (Frontiers in Medicine, 2023)
Interferons were repeatedly used in the therapy of COVID-19 due to their antiviral effects. Three recently published randomized controlled clinical phase III trials (WHO SOLIDARITY, ACTT-3, and SPRINTER) missed their primary objectives, i.e., a significant therapeutic effect of interferons was not demonstrated in these studies. In only one randomized controlled phase III trial (TOGETHER), a significant reduction in the hospitalization rate was revealed. Our study analyzes these findings, gives possible explanations for the failure of interferons, provides a proposal on how these agents could be successfully used, and also highlights the limitations of their employment in COVID-19. Interferons are apparently beneficial only if the patients are in the early stage of this disease and when they are usually not hospitalized, i.e., if the patients do not require oxygen support and/or if corticosteroids are not yet indicated. Furthermore, a higher dosage than the one used in the long-term treatment of multiple sclerosis with interferon beta or of chronic viral hepatitis with interferon alpha or lambda should be employed to achieve a better therapeutic effect in COVID-19.